In vitro Antibacterial Activity of Crude Extracts Produced by Endophytic Fungi Isolated from Piper hispidum Sw. - Orlandelli, R.C., Alberto, R.N., Almeida, T.T., Azevedo, J.L. and Pamphile, J.A. (Journal of Applied Pharmaceutical Science)
Endophytic fungi inhabit the interior of plants without causing apparent harm to them and constitute an alternative for the control of human pathogens, since they can synthesize bioactive compounds. The plant Piper hispidum Sw. has several medicinal properties and harbors a diversity of endophytes. In this present study, four endophytic fungi from P. hispidum were used for obtaining crude ethyl acetate extracts that were tested against Enterococcus hirae, Escherichia coli, Micrococcus luteus, Salmonella typhi and Staphylococcus aureus, using cup plate technique. The obtainment resulted in crude ethyl acetate extracts with a final concentration between 19.9 and 61.4 mg/ml. the antibacterial tests presented satisfactory results, where the pathogenic bacteria were inhibited by the four extracts tested, except for E. hirae that was inhibited by two extracts. Means of inhibition halos ranged from 9.42±0.63 to 14.08±1.70 mm. Analysis of variance showed that the extract produced by endophyte Lasiodiplodia theobromae was the most effective against all bacteria except for S. typhi, which was more inhibited by the extract of an endophyte from Diaporthales order. Therefore, this study indicates that endophytes from medicinal plant P. hispidum could be potential sources of antibacterial substances, with emphasis on L. theobromae.
Keywords: Antimicrobial action, cup plate, fungal extracts, endophytes, Lasiodiplodia theobromae, pathogenic bacteria.